Development of Crash Prediction Models for Short-Term Durations (The National Academies Press, 2023)
Crash prediction methods, which are used to identify crash hotspots or crash severity, consist of safety performance functions (SPFs), crash modification factors, and severity distribution functions. These tools use annual average daily traffic data along with geometric and operational characteristics to predict the annual average crash frequency. NCHRP Research Report 1073: Development of Crash Prediction Models for Short-Term Durations, from TRB's National Cooperative Highway Research Program, provides roadway safety practitioners within state departments of transportation with short-term crash prediction models to be used for estimating safety performance. Supplemental to the report are a Training Materials Presentation, a Webinar Presentation, crash-prediction data on Github, and a crash prediction tool and guide at AASHTO.
Keywords: Transportation and Infrastructure

Advancing Antiracism, Diversity, Equity, and Inclusion in STEMM Organizations: Beyond Broadening Participation - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Individuals from minoritized racial and ethnic groups continue to face systemic barriers that impede their ability to access, persist, and thrive in science, technology, engineering, mathematics, and medicine (STEMM) higher education and workforce. Without actively dismantling policies and practices that disadvantage people from minoritized groups, STEMM organizations stand to lose much needed talent and innovation as well as the ideas that come from having a diverse workforce. A new report from the Board on Behavioral, Cognitive, and Sensory Sciences examines the backdrop of systemic racism in the United States that has harmed and continues to harm people from minoritized groups, which is critical for understanding the unequal representation in STEMM. The report outlines actions that top leaders and gatekeepers in STEMM organizations, such as presidents and chief executive officers, can take to foster a culture and climate of antiracism, diversity, equity, and inclusion that is genuinely accessible and supportive to all.
Keywords: Behavioral and Social Sciences

Evaluation of Compensation Data Collected Through the EEO-1 Form - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The U.S. Equal Employment Opportunity Commission (EEOC) expanded EEO-1 data collection for reporting years 2017 to 2018 in an effort to improve its ability to investigate and address pay disparities between women and men and between different racial and ethnic groups. These pay disparities are well documented in national statistics. For example, the U.S. Census Bureau (2021) found that Black and Hispanic women earned only 63 percent and 55 percent as much, respectively, of what non-Hispanic White men earned. Evaluation of Compensation Data Collected Through the EEO-1 Form examines the quality of pay data collected using the EEO-1 form and provides recommendations for future data collection efforts. The report finds that there is value in the expanded EEO-1 data, which are unique among federal surveys by providing employee pay, occupation, and demographic data at the employer level. Nonetheless, both short-term and longer-term improvements are recommended to address significant concerns in employer coverage, conceptual definitions, data measurement, and collection protocols. If implemented, these recommendations could improve the breadth and strength of EEOC data for addressing pay equity, potentially reduce employer burden, and better support employer self-assessment.
Keywords: Behavioral and Social Sciences

Long-Term Roadside Crash Data Collection Program - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
In 2019, there were more than 10,000 traffic-related fatalities due to single-vehicle run-off-road (ROR) crashes in the United States. Improved roadside crash data are crucial to reduce the severity and frequency of these crashes. NCHRP Research Report 1033: Long-Term Roadside Crash Data Collection Program, from TRB's National Cooperative Highway Research Program, presents an expanded long-term crash data collection program for single-vehicle ROR crashes and conditions associated with them. Supplemental to the report are NCHRP Web-Only Document 341: Roadside Database Coding Manual and a summary presentation.
Keywords: Transportation and Infrastructure

Long-Term Vegetation Management Strategies for Roadsides and Roadside Appurtenances - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Long-term vegetation management strategies that decrease the need for routine chemical and mechanical vegetation control can reduce recurring maintenance costs, highway worker exposure to traffic, impacts to the environment and cultural resources, and maintenance-related delays to the traveling public. However, these strategies vary in their effectiveness, longevity, initial construction costs, maintenance requirements, and aesthetic values.The TRB National Cooperative Highway Research Program's NCHRP Web-Only Document 350: Long-Term Vegetation Management Strategies for Roadsides and Roadside Appurtenances presents information on strategies that control the establishment and growth of roadside vegetation over an extended period, reducing the need for herbicides, mowing, and other mechanical controls.Supplemental to the document are a Selection Tool, a Factsheet, and a Presentation.
Keywords: Transportation and Infrastructure

Addressing the Long-Term Effects of the COVID-19 Pandemic on Children and Families - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The COVID-19 pandemic has had an unprecedented impact on the lives of children and their families, who have faced innumerable challenges such as illness and death; school closures; social isolation; financial hardship; food insecurity; deleterious mental health effects; and difficulties accessing health care. In almost every outcome related to social, emotional, behavioral, educational, mental, physical, and economic health and well-being, families identifying as Black, Latino, and Native American, and those with low incomes, have disproportionately borne the brunt of the negative effects of the pandemic. The effects of the COVID-19 pandemic on children and families will be felt for years to come. While these long-term effects are unknown, they are likely to have particularly significant implications for children and families from racially and ethnically minoritized communities and with low incomes. Addressing the Long-Term Effects of the COVID-19 Pandemic on Children and Families identifies social, emotional, behavioral, educational, mental, physical, and economic effects of the COVID-19 pandemic and looks at strategies for addressing the challenges and obstacles that the pandemic introduced for children and families in marginalized communities. This report provides recommendations for programs, supports, and interventions to counteract the negative effects of the pandemic on child and family well-being and offers a path forward to recover from the harms of the pandemic, address inequities, and prepare for the future.
Keywords: Behavioral and Social Sciences

Long-Term Infrastructure Program Letter Report: January 27, 2023 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
A January 31, 2023 letter report from TRB's Committee for the Review of Federal Highway Administration (FHWA) Infrastructure R&D Program's Long-Term Infrastructure Program (LTIP) summarizes recent program progress, strategic issues, and committee recommendations for future actions. The program has produced some useful products and results over the past year. Although FHWA’s infrastructure research and development is considerably broader than the LTIP, the latter is the sole focus of this committee’s efforts. The LTIP collects long-term performance data on the condition of bridges and pavements that are valuable for guiding decisions regarding the maintenance, repair, and replacement of vital transportation infrastructure assets.
Keywords: Transportation and Infrastructure

Barriers, Challenges, and Supports for Family Caregivers in Science, Engineering, and Medicine: Proceedings of Two Symposia - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Before the COVID-19 pandemic, research demonstrated a significant impact of family caregiving responsibilities on the careers of professionals who work in science, technology, engineering, mathematics, and medicine (STEMM) - especially women. The COVID-19 pandemic increased public recognition of the challenges experienced by caregivers in STEMM fields and created a sense of urgency among many stakeholders. As part of the information-gathering stage of a forthcoming consensus study to address the barriers faced by caregivers, of all genders, in STEMM fields, the Committee on Policies and Practices for Supporting Family Caregivers Working in Science, Engineering, and Medicine organized two national symposia on February 27 and March 27, 2023. Scholars and leaders from a range of sectors convened to identify evidence-based interventions that can support the recruitment, retention, and advancement of caregivers in science, engineering, and medical fields. This publication summarizes the presentations and discussion of the symposia.
Keywords: Policy for Science and Technology

NSF Efforts to Achieve the Nation's Vision for the Materials Genome Initiative: Designing Materials to Revolutionize and Engineer Our Future (DMREF) - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The Materials Genome Initiative (MGI) was launched in 2011 by the White House Office of Science and Technology Policy to help accelerate the design, discovery, development and deployment of advanced materials and to reduce costs through the integration of advanced computation and data management with experimental synthesis and characterization. A broad range of federal agencies - including the National Science Foundation (NSF), the Department of Energy, and the Department of Defense - are part of the MGI effort and have invested more than $1 billion in resources and infrastructure accumulative since the start. The efforts of NSF have been focused largely within the Designing Materials to Revolutionize and Engineer Our Future (DMREF) program, which supports the development of fundamental science, computational and experimental tools for generating and managing data, and workforce that enable industry and other government agencies to develop and deploy materials that meet societal needs and national priorities. At the request of NSF, this report evaluates the goals, progress, and scientific accomplishments of the DMREF program within the context of similar efforts both within the United States and abroad. The recommendations of this report will assist NSF as it continues to increase its engagement with industry and federal agencies to transition the results from fundamental science efforts to reach the MGI goal of deploying advanced materials at least twice as fast as possible today, at a fraction of the cost that meet national priorities.
Keywords: Engineering and Technology

Nuclear Proliferation and Arms Control Monitoring, Detection, and Verification: A National Security Priority: Summary of the Final Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Robust monitoring, detection, and verification capabilities are necessary to provide decision makers with critical information regarding nuclear threats and to support deterrence and nonproliferation by uncovering efforts to clandestinely develop a nuclear capability or enhance an existing capability. The United States has significant capabilities to monitor, detect, and verify nuclear weapons and fissile material production in foreign states, but in order to address future challenges and avoid surprises, these capabilities must be strengthened and maintained through research and development and operationalization of new technologies. Congress tasked the National Academies of Sciences, Engineering, and Medicine to undertake an independent review and assessment of the United States capabilities for monitoring, detection, and verification of nuclear weapons and fissile material in the fiscal year 2020 National Defense Authorization Act. The study committee released an extensive interim report in April 2021 after an initial phase of data gathering. Following an additional data-gathering period that included examining restricted information unavailable to the committee during the initial phase of the project, the committee produced a final report in January 2023. In that report, the committee reassessed the findings and recommendations made in its interim report and found them to be supported and confirmed by the additional information. This document, the public summary of the final report, reproduces the findings and recommendations from the interim report and includes the committee’s commentary regarding many of the interim report findings and recommendations after additional data gathering.
Keywords: Conflict and Security Issues

Intergenerational Poverty and Mobility Among Native Americans in the United States: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
On July 22 and 25, 2022, the National Academies of Sciences, Engineering, and Medicine held an information gathering meeting titled, Intergenerational Poverty and Mobility Among Native Americans in the U.S. The meeting was held to inform the future consensus report of the National Academies Committee on Policies and Programs to Reduce Intergenerational Poverty. Building on the findings of the 2019 report, A Roadmap to Reducing Child Poverty, this ad hoc committee was convened by the Board on Children, Youth, and Families to identify policies and programs with the potential to reduce long-term, intergenerational poverty. The harmful effects of living in poverty during childhood can entrench families and communities in poverty, leading to the transmission of poverty from one generation to the next. This cycle has a disproportionate effect on Native American families. This public information-gathering meeting was held to engage with leaders, researchers, and practitioners on issues surrounding intergenerational poverty and mobility among Native American families in the United States, including exploring key structural determinants of entrenched poverty and promising interventions designed to address those determinants.
Keywords: Behavioral and Social Sciences

Toward Sequencing and Mapping of RNA Modifications: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
One strategy cells use for regulation is modifying proteins, DNA, and RNA to control their structure, function, and stability. For years, research has focused on the reversible modifications to proteins and DNA. However, RNA can also be highly modified, and more than 170 types of modification to RNA have been identified so far. Current methods for mapping and sequencing RNA and its modifications - also known as the epitranscriptome - are limited, partly because available sequencing technologies can detect only a small number of them. This limits the understanding of different molecular processes and leaves a gap in knowledge related to human diseases and disorders. To address these limitations and develop a roadmap for the sequencing of RNA with the epitranscriptome, the National Academies of Sciences, Engineering, and Medicine convened an ad hoc committee to provide a consensus report. A workshop held on March 14-15, 2023 was one part of an information-gathering effort by the committee and is summarized in this proceedings.
Keywords: Biology and Life Sciences

Climate Security in South Asia: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The South Asia region presents a confluence of major climate impacts and key security issues. From a weather and climate standpoint, the region experiences a wide range of hazards, such as the recent heatwaves, droughts, storms, and floods that have upended the lives and livelihoods of millions of people. From a demographic and socioeconomic standpoint, the region is experiencing rapid transformations and progress, even as fundamental challenges such as poverty and inequality persist. From a security standpoint, the region is the setting for a range of social and political dynamics that impact U.S. interests, including conflict at national and subnational levels; regional rivalries; and the imprint of global geopolitics. On October 26-27, 2022, the National Academies of Sciences, Engineering, and Medicine, under the auspices of the National Academies Climate Security Roundtable, convened a workshop to explore climate security in South Asia. Over two days, workshop participants considered some of the underlying climate, development, and geopolitical dynamics at play in the South Asia region; explored a set of historical case studies and future scenarios for climate change and security in South Asia; and they considered the available tools for analysis and forecasting climate-related risks. This publication summarizes the presentations and discussion of the workshop.
Keywords: Environment and Environmental Studies

An Assessment of Native Seed Needs and the Capacity for Their Supply: Final Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Extreme weather and wildfires, intensified by climate change, are damaging the native plant communities of landscapes across the United States. Native plant communities are foundational to thriving ecosystems, delivering goods and services that regulate the environment and support life, provide food and shelter for a wide range of native animals, and embody a wealth of genetic information with many beneficial applications. Restoring impaired ecosystems requires a supply of diverse native plant seeds that are well suited to the climates, soils, and other living species of the system. This report examines the needs for native plant restoration and other activities, provides recommendations for improving the reliability, predictability, and performance of the native seed supply, and presents an ambitious agenda for action. An Assessment of Native Seed Needs and the Capacity for Their Supply considers the various challenges facing our natural landscapes and calls for a coordinated public-private effort to scale-up and secure a cost-effective national native seed supply.
Keywords: Agriculture

Crime Rates During the COVID-19 Pandemic: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The National Academies of Sciences, Engineering, and Medicine Committee on Law and Justice convened a workshop through its Planning Committee on Crime Rates during the SARS-CoV-2 or COVID-19 pandemic on November 10, 2022, to explore crime rate changes during the pandemic, potential explanations for those rates, and opportunities for future methods, data, and research. Specifically, it sought to (1) explore existing data on the trends in multiple criminal offenses during the pandemic; (2) explore existing explanations for the crime rate changes in multiple offense types during the pandemic for their scope, logical consistency, empirical support, and limitations, with special attention to explanations related to the pandemic and associated population restrictions (e.g., stay at home orders, social gathering restrictions, etc.), as well as the diffusion and availability of firearms; and (3) discuss methodological issues, data infrastructure needs, and research gaps to inform understanding of crime problems and rates. This publication summarizes the presentation and discussion of the workshop.
Keywords: Behavioral and Social Sciences

Opportunities and Challenges for Digital Twins in Atmospheric and Climate Sciences: Proceedings of a Workshop—in Brief - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The digital twin is an emerging technology that builds on the convergence of computer science, mathematics, engineering, and the life sciences. Digital twins have the potential to revolutionize atmospheric and climate sciences in particular, as they could be used, for example, to create global-scale interactive models of Earth to predict future weather and climate conditions over longer timescales. On February 1-2, 2023, the National Academies of Sciences, Engineering, and Medicine hosted a public, virtual workshop to discuss characterizations of digital twins within the context of atmospheric, climate, and sustainability sciences and to identify methods for their development and use. Workshop panelists presented varied definitions and taxonomies of digital twins and highlighted key challenges as well as opportunities to translate promising practices to other fields. The second in a three-part series, this evidence-gathering workshop will inform a National Academies consensus study on research gaps and future directions to advance the mathematical, statistical, and computational foundations of digital twins in applications across science, medicine, engineering, and society.
Keywords: Earth Sciences; Computers and Information Technology; Math, Chemistry, and Physics; Engineering and Technology

Intergenerational Poverty and Mobility Among Native Americans in the United States: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Experiencing poverty during childhood can lead to lasting harmful effects in which poverty is passed on to future generations - a cycle that disproportionately affects Native American families. To identify policies and programs that can reduce long-term, intergenerational poverty among Native Americans in the United States, the Board on Children, Youth, and Families held information-gathering sessions on July 22, 2022 and July 25, 2022. In these sessions, key historical and structural factors that lead to entrenched poverty were examined as well as promising interventions for addressing them. Importantly, these sessions included a conversation with community leaders on their experiences with and work on intergenerational poverty as well as key data and trends on this topic.
Keywords: Behavioral and Social Sciences

Emerging Stronger from COVID-19: Priorities for Health System Transformation - National Academy of Medicine (The National Academies Press, 2023)
In mid-2022, the United States has lost more than 1 million people to the COVID-19 pandemic. We have been real-time witnesses to scores of heroic responses to the disease, death, inequity, and economic strife unleashed by the virus, but have also experienced the consequences of poor pandemic preparedness and long-standing structural failures in our health system. For decades, the U.S. health system has fallen far short of its potential to support and improve individual and population health. The COVID-19 pandemic has presented death and devastation—but also an unprecedented opportunity to truly transform U.S. health, health care, and health delivery. To capitalize on this opportunity, the National Academy of Medicine gathered field leaders from across all of the major health system sectors to assess how each sector has responded to the pandemic and the opportunities that exist for health system transformation. The opportunity is now to capitalize on the hard-won lessons of COVID-19 and build a health care system that centers patients, families, and communities; cares for clinicians; supports care systems, public health, and biomedical research to perform at the best of their abilities; applies innovations from digital health and quality, safety, and standards organizations; and encourages health care payers and health product manufacturers and innovators to produce products that benefit all.
Keywords: Health and Medicine

Inclusion of Pregnant and Lactating Persons in Clinical Trials: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Approximately 4 million pregnant people in the United States give birth annually, and 70 percent of these individuals take at least one prescription medication during their pregnancy. Yet, due to a number of historical, ethical, legal, scientific, and societal issues, pregnant and lactating persons are often excluded from clinical trials. As a result, pregnant and lactating persons are often taking drugs based on limited information about the benefits and risks to themselves and their developing or newborn baby. The National Academies Forum on Drug Discovery, Development, and Translation convened a workshop in June 2022 for stakeholders to examine the current state of evidence generation for drug products used by pregnant and lactating persons and discuss barriers and opportunities for including these populations in clinical trials. This publication summarizes the presentations and discussion of the workshop.
Keywords: Health and Medicine

Confucius Institutes at U.S. Institutions of Higher Education: Waiver Criteria for the Department of Defense - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
More than 100 U.S. institutions of higher education hosted Confucius Institutes (CIs), Chinese government-funded language and culture centers, on campus during the late 2000s and 2010s. While CIs provided a source of funding and other resources that enabled U.S. colleges and universities to build capacity, offer supplemental programming, and engage with the local community, CIs presented an added, legitimate source of risk to host institutions with respect to academic freedom, freedom of expression, and national security. By 2017, deteriorating U.S.-China relations led some U.S. colleges and universities to reconsider the value of having a CI on campus. Sustained interest by Congress and political pressure led numerous U.S.-based CIs to close, especially following the passage of the Fiscal Year 2019 National Defense Authorization Act, which contained a provision that ultimately barred institutions receiving Department of Defense (DOD) critical language flagship funding in Chinese from hosting a CI. While this provision allowed for a waiver process - and several affected colleges and universities applied for waivers in 2018 and 2019 - DOD did not issue any waivers. Today, seven CIs remain on U.S. university and college campuses. At the request of DOD, Confucius Institutes at U.S. Institutions of Higher Education presents a set of findings and recommendations for waiver criteria to potentially permit the continued presence of CIs on U.S. university campuses that also receive DOD funding.
Keywords: Policy for Science and Technology; Education